Crew resource management training : a competence-based approach for airline pilots - MacLeod, Norman, 1954- (Boca Raton : CRC Press, 2021)
"The book provides a data-driven approach to real-world CRM applicable to commercial pilot performance. It addresses the shift to a systems-based resilience thinking that aims to understand how worker performance provides a buffer against failure. This book will be the first to bring these ideas together. Taking a competence-based approach offers a more coherent, relevant approach to CRM. The book presents relevant, real world examples of the concepts and outlines a change in thinking around pilot performance and interpretation of data that is overdue. Airlines, pilots, and aviation industry professionals will benefit from the insights into organizational design and alternative approaches to training"--
OCLC-licensed vendor bibliographic record.
Keywords: Flight crews -- Management -- Study and teaching; Air pilots -- Training of; Aeronautics, Commercial -- Employees -- Personnel management; Instructional systems -- Design; BUSINESS & ECONOMICS / Human Resources & Personnel Management; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Health & Safety